The G protein-coupled estrogen receptor (GPER/GPR30) may serve as a prognostic marker in early-stage cervical cancer - Friese, Klaus; Marmé, Frederik; Heublein, Sabine (Journal of cancer research and clinical oncology, 2018)
BackgroundEstrogen signalling is transmitted via various receptors and multiple intracellular signalling pathways. Estrogen receptor alpha (ERα)-mediated transcription of target genes has been demonstrated to be closely linked to human papilloma virus (HPV)-induced carcinogenesis in case of cervical cancer. So far, the role of non-genomic estrogen signals in cervical cancer, e.g. transmitted by the G protein-coupled estrogen receptor (GPER) remains to be rather elusive. Today’s knowledge on the role of GPER in cervical cancer is sparse and—to the best of our knowledge—GPER has not been investigated in context with clinicopathological parameters or prognosis of cervical cancer. Therefore, the current study investigated whether GPER is expressed in cervical cancer tissue. Further, GPER was correlated to clinicopathological parameters, tissue markers of cervical carcinogenesis and to patient overall and recurrence-free survival.Materials and methodsCervical cancer tissue was collected from 156 patients during surgery between 1993 and 2002. GPER immunostaining was performed on all the cases and correlated to clinicopathological data. More than half of all patients were diagnosed at advanced stage (FIGO II-IV 93/156; 59.6%) of disease. The large majority of patients presented with tumours of intermediate or high grade (G2-3 140/152, 92.1%). 22 cervical cancer-related deaths (22/156, 14.1%) were documented during the follow-up period.ResultsGPER was detected in various subcellular staining patterns. In 129/156 (82.7%) cases GPER was expressed in the tumour cell cytoplasm (GPERcyt). GPER immunopositivity at the cell membrane (GPERmem) was found in 114/156 (73.1%) cases. While co-occurrence of both membrane and cytoplasmic staining (GPERcyt + GPERmem) was detected in the majority of tissue samples (101/156; 64.7%), only few cases (14/156, 9.0%) were classified as not expressing GPER at all. GPERcyt was positively correlated with tumour grade. Statistical associations of GPER and both p16 and p53 were detected. Finally, immunopositivity of GPERcyt was predictive for favourable overall as well as recurrence-free survival in cervical cancer of early stage (FIGO I).ConclusionThis retrospective study reports GPERcyt to be associated with improved overall and recurrence-free survival in early-stage cervical cancer. Further investigations are needed thus to determine whether this observation may be of clinical impact. Interestingly, Raloxifene—a GPER-activating selective estrogen receptor modulator—has recently been demonstrated to be preventive for cervical cancer relapse in mice. Whether this effect is only reliant on raloxifene blocking ERα or may also be related to activation of GPER remains to be determined.
Published online: 18 September 2017
Gesehen am 25.07.2019